Badminton men's singles match final racket motion and scoring rate regression analysis - Gao, J.; Huang, Y.; Huang, Q. (BioTechnology: An Indian Journal, 2014)
Badminton match final racket motion is very crucial to badminton match's result. Look for relations between badminton final racket motion and badminton match gains and losses are surely very important to athlete technical training. Especially for comparable players' matches, players' final racket motions will become the focus. The paper takes world top men's badminton singles players as research objects. Adopt simple linear regression model, and use SPSS software to make research on final racket motion and scoring rate relationships. Utilize least square method solution on simple linear regression equation parameters to calibrate solved model`s parameters. Therefore it gets badminton final racket motion and badminton match gains and losses relationship, which has important significances in future badminton players' technical and tactics training. (c) Abstract by Trade Science Inc. - INDIA